TOTUM‐63, a plant‐based polyphenol‐rich extract, improves glycaemic control in subjects with prediabetes or early stage newly‐diagnosed type 2 diabetes in a randomized, double‐blind, placebo‐controlled trial - Sirvent, Pascal; Chavanelle, Vivien; Otero, Yolanda F.; Bargetto, Maxime; Le Joubioux, Florian; Boisseau, Nathalie; Maugard, Thierry; Cazaubiel, Murielle; Pereira, Bruno; Guigas, Bruno; Hadjadj, Samy; Peltier, Sebastien L.; et al. (Diabetes, obesity & metabolism, 2022)
Aim The plant‐based polyphenol‐rich extract TOTUM‐63 improves glucose homeostasis in various preclinical models of obesity and type 2 diabetes (T2D). A pilot exploratory study showed that TOTUM‐63 has good safety and tolerability profiles, and beneficial effects on postprandial glucose control in healthy individuals with overweight. The aim of this study was to assess the effects of TOTUM‐63 on glycaemic control in individuals with prediabetes or early stage newly‐diagnosed T2D (which does not require pharmacological treatment). Materials and Methods This study was a multicentre, randomized, double‐blind, placebo‐controlled trial. Individuals with prediabetes or early stage newly‐diagnosed T2D and with overweight/abdominal obesity received TOTUM‐63 (5 g/day) or placebo for 6 months. The primary outcome was the change in fasting blood glucose. Results Fifty‐one participants (age: 57.1 ± 10 years; body mass index: 31.3 ± 5.7 kg.m2; 35 women and 16 men) completed the study (n = 38 TOTUM‐63, n = 13 placebo). After 6 months, blood glucose concentration after fasting and after the 2‐h oral glucose tolerance test was reduced in the TOTUM‐63‐treated group compared with the placebo group (placebo‐corrected difference between baseline and month 6: −0.71 mmol/L, p < .05, and −1.93 mmol/L, p < .05, respectively). TOTUM‐63 was safe and well tolerated and significantly reduced body weight gain (−1.9 kg; p < .05), waist circumference (−4.5 cm; p < .001), circulating triglycerides (−0.54 mmol/L; p < .01) and low‐density lipoprotein‐cholesterol (−0.38 mmol/L; p < .05) compared with placebo. Conclusions TOTUM‐63 lowered fasting blood glucose in participants with impaired fasting glycaemia and glucose intolerance. Moreover, TOTUM‐63 showed a good safety and tolerability profile and improved several metabolic syndrome features. Therefore, TOTUM‐63 is a promising candidate for T2D prevention.